Metabolic Fingerprint of PS3-Induced Resistance of Grapevine Leaves against Plasmopara viticola Revealed Differences in Elicitor-Triggered Defenses - Adrian, Marielle; Lucio, Marianna; Roullier-Gall, Chloé; Héloir, Marie-Claire; Trouvelot, Sophie; Daire, Xavier; Kanawati, Basem; Lemaître-Guillier, Christelle; Poinssot, Benoît; Gougeon, Régis; Schmitt-Kopplin, Philippe (Frontiers in Plant Science, 2017)
Induction of plant resistance against pathogens by defense elicitors constitutes an attractive strategy to reduce the use of fungicides in crop protection. However, all elicitors do not systematically confer protection against pathogens. Elicitor-induced resistance (IR) thus merits to be further characterized in order to understand what makes an elicitor efficient. In this study, the oligosaccharidic defense elicitors H13 and PS3, respectively ineffective and effective to trigger resistance of grapevine leaves against downy mildew, were used to compare their effect on the global leaf metabolism. Ultra high resolution mass spectrometry (FT-ICR-MS) analysis allowed us to obtain and compare the specific metabolic fingerprint induced by each elicitor and to characterize the associated metabolic pathways. Moreover, erythritol phosphate was identified as a putative marker of elicitor-IR.